Preparation process of non-woven fabric grinding pad and product

By pretreating the non-woven abrasive pad and immersing the water-based polyurethane, and performing shaping, bristling and groove treatment, the problem of insufficient penetration and flow performance of the non-woven abrasive pad on the abrasive liquid is solved, and efficient grinding effect and long life are achieved.

CN119567121AActive Publication Date: 2025-03-07DONGGUAN LIZHI GRINDING TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411753468.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-07
Estimated Expiration
2044-12-02

AI Technical Summary

Technical Problem

The conventional non-woven abrasive pad has low penetration and flow performance on the abrasive liquid, resulting in a reduced grinding efficiency and service life.

Method used

The dry-formed polyester nonwoven fabric is pretreated with a pretreatment agent, followed by impregnation treatment using an aqueous polyurethane impregnation liquid, and shaping, bristle and groove treatments are carried out to improve the overall strength of the grinding pad and the flow performance of the grinding liquid.

Benefits of technology

The flow and permeability of the non-woven abrasive pad to the abrasive liquid is improved, the grinding efficiency and service life are improved, and the flexibility and grinding strength of the abrasive pad are maintained.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119567121A_ABST
    Figure CN119567121A_ABST
Patent Text Reader

Abstract

The invention relates to the field of grinding materials, and discloses a preparation process of a non-woven fabric grinding pad and a product. The preparation technology of the non-woven fabric grinding pad comprises the following steps that S1, polyester non-woven fabric formed through a dry method is soaked with a pretreating agent, and pretreated polyester non-woven fabric is prepared; s2, carrying out dipping treatment on the pretreated polyester non-woven fabric by using a waterborne polyurethane dipping solution, rolling and drying to obtain a dipped polyester non-woven fabric; s3, the prepared impregnated polyester non-woven fabric is subjected to shaping, sanding, slotting, water washing and drying, and the non-woven fabric grinding pad is prepared; according to the preparation technology, the polyester non-woven fabric formed through the dry method is subjected to the preparation technology of pretreatment, dipping, sizing, sanding and slotting, in the grinding process of the prepared non-woven fabric grinding pad, grinding liquid has good circulation and permeability, the grinding efficiency is high, and the service life of the grinding pad is long.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of abrasive materials, and more specifically, to a preparation process and product of a non-woven abrasive pad. Background Art

[0002] Chemical Mechanical Polishing (CMP) is one of the key technologies for semiconductor wafer surface processing and multi-layer wiring interlayer flattening and has been widely used in recent years. The polishing pad is an important part of the CMP system. The material properties and structure of the polishing pad directly affect the performance of the polishing pad, and thus also affect the CMP process and processing effect.

[0003] Non-woven polishing pad is a kind of polishing pad. Non-woven fabric (Non Woven) is also called non-woven fabric. It is composed of directional or random fibers. It is a new generation of environmentally friendly materials with the characteristics of low price and recyclability. Non-woven polishing pads have a strong ability to hold polishing liquid, good mechanical properties, and can achieve good polishing efficiency and service life. They are widely used in precision optics, flat glass, LCD, FPD, storage disk drives, semiconductor ceramic substrates, optical glass, LED sapphire substrates, crystals and other grinding fields. They can grind workpieces of various materials, such as silicon wafers, gallium arsenide, quartz crystals, sapphire, metals, semiconductor materials and other products.

[0004] Common non-woven polishing pads are made by coating or impregnating polyurethane materials on non-woven fabric layers and drying them to improve the hardness, density and mechanical properties of non-woven polishing pads. However, after polyurethane materials are filled into non-woven fabrics, the penetration and flow performance of the polishing liquid on the non-woven polishing pads is reduced, thereby reducing the polishing efficiency and service life of the non-woven polishing pads. Summary of the invention

[0005] In order to solve the problem that conventional non-woven polishing pads have low penetration and flow performance to polishing liquid, thereby reducing the polishing efficiency and service life of the non-woven polishing pad, the present application provides a preparation process and product of a non-woven polishing pad.

[0006] In a first aspect, the present application provides a preparation process of a non-woven polishing pad, using the following technical solution: A preparation process of a non-woven fabric grinding pad comprises the following steps: S1, soaking the dry-formed polyester non-woven fabric with a pretreatment agent to obtain a pretreated polyester non-woven fabric; S2, using an aqueous polyurethane impregnation liquid to impregnate the pretreated polyester non-woven fabric, rolling and drying, to obtain an impregnated polyester non-woven fabric; S3, shaping, sanding, slotting, washing and drying the obtained impregnated polyester non-woven fabric to obtain a non-woven fabric abrasive pad.

[0007] By adopting the above technical scheme, a dry-formed polyester non-woven fabric is used as a carrier, which has good air permeability, elasticity and mechanical strength, and can improve the overall strength of the prepared non-woven fabric polishing pad; firstly, the polyester non-woven fabric is pretreated with a pretreatment agent, and the pretreatment agent can penetrate into the fiber structure of the polyester non-woven fabric, thereby improving the bonding performance between the aqueous polyurethane impregnation liquid and the polyester non-woven fabric fibers in subsequent treatment; then, the prepared pretreated polyester non-woven fabric is impregnated with an aqueous polyurethane impregnation liquid, so that the aqueous polyurethane impregnation liquid penetrates and polymerizes the polyester non-woven fabric. The polyester non-woven fabric is collected into the fiber structure to form a stable skeleton structure, and at the same time, it will not affect the fiber pore structure of the polyester non-woven fabric, further improving the flexibility and grinding strength of the non-woven polishing pad; finally, it is shaped, sanded and slotted. The shaping can improve the dimensional stability of the non-woven polishing pad, the sanding can improve the surface flatness of the non-woven polishing pad, and the slotting can reduce the heat accumulation of the non-woven polishing pad, improve the fluidity of the polishing liquid, further improve the polishing efficiency of the non-woven polishing pad, and then improve the comprehensive performance of the non-woven polishing pad. The non-woven polishing pad prepared in this way has good circulation and permeability to the polishing liquid, improving the grinding efficiency and the service life of the non-woven polishing pad.

[0008] Preferably, the pretreatment agent in step S1 is prepared from the following raw materials in percentage by weight: N,N-Methylenebisacrylamide 8-10% Long chain alkyl silane coupling agent 3-5% Allyl polyethylene glycol 2-3% Chitosan quaternary ammonium salt 1-3% Sodium dioctyl sulfosuccinate 1-2% Water balance.

[0009] By adopting the above technical scheme, N,N-methylenebisacrylamide, long-chain alkyl silane coupling agent, allyl polyethylene glycol, chitosan quaternary ammonium salt and sodium diethyl sulfosuccinate are compounded in an optimal weight ratio, which has a good synergistic effect, can penetrate and disperse into the fiber structure of the polyester non-woven fabric, improve the looseness and adsorption performance of the polyester non-woven fabric, and then improve the bonding performance between the aqueous polyurethane impregnation liquid and the fibers of the polyester non-woven fabric in the subsequent treatment, so that the prepared non-woven polishing pad has good elasticity, flexibility and strength, and forms a pore structure, improves the circulation and penetration performance of the polishing liquid during use, and then improves the polishing efficiency and service life of the non-woven polishing pad; wherein the long-chain alkyl silane coupling agent is a silane coupling agent with 8-16 alkyl groups, which can significantly improve the adsorption and penetration performance of the polyester non-woven fabric fiber to the aqueous polyurethane impregnation liquid.

[0010] Preferably, the soaking temperature in step S1 is 50-60° C., and the soaking time is 20-40 min.

[0011] By adopting the above technical solution and controlling the optimal immersion conditions, the uniform permeability of the pretreatment agent in the polyester non-woven fabric can be improved.

[0012] Preferably, the polyester nonwoven fabric in step S1 has a thickness of 1-1.5 mm and a gram weight of 300-350 g / m 2 .

[0013] By adopting the above technical solution and controlling the specifications and dimensions of the polyester non-woven fabric, the polyester non-woven fabric can be fully impregnated and formed while saving consumables, thereby improving the grinding efficiency and service life of the prepared non-woven fabric polishing pad.

[0014] Preferably, the aqueous polyurethane impregnation liquid in step S2 is prepared from the following raw materials in percentage by weight: Water-based polyurethane emulsion 30-40% Methyl phenyl silicone resin emulsion 5-8% Ethylene-vinyl acetate copolymer emulsion 3-6% Filler 10-15% 1,4-Butanediol dimethacrylate 3-5% Viscosity modifier 2-4% Curing agent 1-3% Water balance.

[0015] By adopting the above technical scheme, the aqueous polyurethane impregnation liquid of the present application uses aqueous polyurethane emulsion as the main body and has good elasticity and flexibility. However, during the grinding process, the non-woven grinding pad will generate heat due to grinding, thereby reducing the hardness and wear resistance of the grinding pad, thereby affecting the grinding efficiency. Therefore, a better amount of methylphenyl silicone resin emulsion and ethylene-vinyl acetate copolymer emulsion are compounded into the aqueous polyurethane emulsion, and the three produce a good synergistic effect, so that the prepared non-woven grinding pad has good flexibility and elasticity while maintaining good heat resistance and grinding strength during the grinding process; 1,4-butylene glycol dimethacrylate can be further cross-linked with the emulsion system, and under the synergistic effect of the filler, the strength and grinding efficiency of the non-woven grinding pad are further improved. Viscosity regulators can effectively improve the viscosity of waterborne polyurethane impregnation liquids. In actual tests, when the amount of emulsion reaches a better ratio, the system viscosity of the waterborne polyurethane impregnation liquid is relatively high, which reduces the stability and timeliness of the impregnation treatment. Therefore, the viscosity regulator allows the emulsion system to have better dispersion and wettability while maintaining better strength and cross-linking stability.

[0016] Preferably, the filler is white carbon black and / or zinc oxide.

[0017] By adopting the above technical solution, white carbon black and / or zinc oxide are selected as fillers, which can improve the strength and wear resistance of the non-woven grinding pad, reduce the wear during the grinding process, and extend the service life of the non-woven grinding pad.

[0018] Preferably, the viscosity modifier is composed of allyl glycidyl ether and 2-acrylamide-2-methylpropane sulfonic acid in a weight ratio of 1:(1-3).

[0019] By adopting the above technical scheme, allyl glycidyl ether and 2-acrylamide-2-methylpropane sulfonic acid in a preferred weight ratio are used as viscosity regulators, which can improve the viscosity of the aqueous polyurethane impregnating liquid, so that it can be evenly adsorbed on the fiber structure of the polyester non-woven fabric during the impregnation process, and at the same time, the curing cross-linking degree is improved when the aqueous polyurethane impregnating liquid is cured, thereby improving the mechanical strength of the non-woven polishing pad while maintaining good polishing liquid permeability and flow performance, thereby improving the polishing efficiency and extending the service life.

[0020] Preferably, the curing agent is an isocyanate curing agent and / or an aziridine curing agent.

[0021] By adopting the above technical solution and selecting an isocyanate curing agent and / or an aziridine curing agent, the curing efficiency of the aqueous polyurethane impregnation liquid can be effectively improved, thereby improving the mechanical properties and durability of the non-woven fabric polishing pad.

[0022] Preferably, the immersion treatment time in step S2 is 30-60 minutes, and the immersion treatment temperature is 70-80°C.

[0023] By adopting the above technical solution and the better impregnation treatment conditions, the aqueous polyurethane impregnation liquid can fully penetrate into the polyester non-woven fabric, thereby improving the uniformity and density of the prepared non-woven fabric polishing pad.

[0024] In a second aspect, the present application provides a non-woven polishing pad, which adopts the following technical solution: A non-woven fabric grinding pad is prepared by the above preparation process.

[0025] By adopting the above technical solution, during the grinding process of the non-woven fabric grinding pad prepared in the present application, the grinding liquid has good circulation and penetration performance, the grinding efficiency is high, and the service life of the grinding pad is long.

[0026] In summary, this application has the following beneficial effects: 1. The preparation process of the non-woven polishing pad of the present application is to pretreat the dry-formed polyester non-woven fabric with a pretreatment agent, and then impregnate it with an aqueous polyurethane impregnation liquid; finally, it is shaped, sanded and grooved. During the grinding process, the prepared non-woven polishing pad has good circulation and penetration properties of the polishing liquid, high grinding efficiency, and a long service life of the polishing pad.

[0027] 2. By using a pretreatment agent made of N,N-methylenebisacrylamide, long-chain alkyl silane coupling agent, allyl polyethylene glycol, chitosan quaternary ammonium salt, sodium diethyl sulfosuccinate and water, the looseness and adsorption performance of the polyester non-woven fabric are improved, thereby improving the bonding performance between the aqueous polyurethane impregnation liquid and the polyester non-woven fabric fibers in the subsequent treatment, so that the prepared non-woven polishing pad has good elasticity, flexibility and strength, and forms a pore structure, which improves the circulation and penetration performance of the polishing liquid during use, thereby improving the polishing efficiency and service life of the non-woven polishing pad.

[0028] 3. By using an aqueous polyurethane impregnation liquid prepared from aqueous polyurethane emulsion, methylphenyl silicone resin emulsion, ethylene-vinyl acetate copolymer emulsion, filler, 1,4-butylene glycol dimethacrylate, viscosity regulator, curing agent and water, the aqueous polyurethane impregnation liquid penetrates and aggregates into the fiber structure of the polyester non-woven fabric to form a structurally stable skeleton structure, while not affecting the fiber pore structure of the polyester non-woven fabric, thereby further improving the flexibility and grinding strength of the prepared non-woven polishing pad.

[0029] 4. By using allyl glycidyl ether and 2-acrylamide-2-methylpropane sulfonic acid in an optimal weight ratio as a viscosity regulator, the viscosity of the aqueous polyurethane impregnation liquid can be improved, so that it can be evenly adsorbed on the fiber structure of the polyester non-woven fabric during the impregnation process, while improving the mechanical strength of the non-woven polishing pad while maintaining good polishing liquid permeability and flow performance, thereby improving the polishing efficiency and extending the service life. BRIEF DESCRIPTION OF THE DRAWINGS Attached Figure 1 This is a scanning electron microscope image of the non-woven fabric polishing pad of the present application at 100 μm. DETAILED DESCRIPTION

[0031] The following is combined with Figure 1 The present application is further described in detail with reference to the accompanying drawings and embodiments.

[0032] The following are the sources and specifications of some raw materials of this application. The raw materials used in the preparation examples and embodiments of this application can be obtained from the market, including but not limited to the raw materials of the following models and manufacturers. Raw materials with equivalent performance can be used: 1. Chitosan quaternary ammonium salt: Tosoh Chemical HACC-102; 2. Water-based polyurethane emulsion: Anda Huatai AH-1619; 3. Methylphenyl silicone resin emulsion: Sihai SH-9608; 4. Ethylene-vinyl acetate copolymer emulsion: Wacker EP701K, Germany; 5. White carbon black: fumed silica, particle size 100-200nm; 6. Zinc oxide: particle size 100-200nm; 7. 1,4-Butanediol dimethacrylate: CAS No. 2082-81-7, content 99%; 8. 2-Acrylamide-2-methylpropanesulfonic acid: CAS No. 15214-89-8, content 99%; 9. Isocyanate curing agent: Bayhydur 304; 10. Aziridine curing agent: XR-100.

[0033] Preparation Example of Pretreatment Agent Preparation Example 1 Preparation Example 1 discloses a pretreatment agent, which is prepared by the following steps: 0.8 kg N, N-methylenebisacrylamide, 0.3 kg dodecyltrimethoxysilane as a long-chain alkylsilane coupling agent, 0.3 kg allyl polyethylene glycol, 0.1 kg chitosan quaternary ammonium salt, and 0.1 kg sodium diisooctyl sulfosuccinate were added to 8.4 kg water and stirred evenly to prepare a pretreatment agent.

[0034] Preparation Example 2-3 The difference between Preparation Example 2-3 and Preparation Example 1 is that the amount of raw materials used and the preparation conditions are different, see Table 1 below for details.

[0035] Table 1 Parameters of Preparation Examples 1-3 Preparation Comparative Example 1 The difference between Preparation Comparative Example 1 and Preparation Example 1 is that an equal amount of N,N-methylenebisacrylamide is replaced by N,N-dimethylformamide, and the rest is the same as Preparation Example 1.

[0036] Preparation Comparative Example 2 The difference between Preparation Comparative Example 2 and Preparation Example 1 is that the long-chain silane coupling agent is replaced by an equal amount of a short-chain silane coupling agent, and the short-chain silane coupling agent is vinyltrimethoxysilane. The rest is the same as Preparation Example 1.

[0037] Preparation Comparative Example 3 The difference between Preparation Comparative Example 3 and Preparation Example 1 is that the chitosan quaternary ammonium salt is replaced by allyl polyethylene glycol in equal amounts, and the rest is the same as Preparation Example 1.

[0038] Preparation Comparative Example 4 The difference between Preparation Comparative Example 4 and Preparation Example 1 is that an equal amount of allyl polyethylene glycol is replaced by N,N-methylenebisacrylamide, and the rest is the same as Preparation Example 1.

[0039] Preparation Example of Waterborne Polyurethane Impregnation Solution Preparation Example 4 Preparation Example 4 discloses an aqueous polyurethane impregnation solution, which is prepared by the following steps: 3kg of aqueous polyurethane emulsion, 0.8kg of methylphenyl silicone resin emulsion, 0.6kg of ethylene-vinyl acetate copolymer emulsion, 0.3kg of 1,4-butylene glycol dimethacrylate and 1kg of white carbon black were added as fillers into 3.9kg of water, and stirred for 30min at a stirring rate of 400r / min; 0.3kg of viscosity regulator (composed of 0.15kg of allyl glycidyl ether and 0.15kg of polyethylene glycol 400) and 0.1kg of curing agent (composed of 0.05kg of isocyanate curing agent and 0.05kg of aziridine curing agent) were added, and stirred for 20min at a stirring rate of 400r / min to obtain an aqueous polyurethane impregnation liquid.

[0040] Preparation Example 5-6 The difference between Preparation Example 5-6 and Preparation Example 4 is that the amount of raw materials used and the preparation conditions are different, see Table 2 below for details.

[0041] Table 2 Parameters of Preparation Examples 4-6 Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 4 is that the viscosity modifier consists of allyl glycidyl ether and 2-acrylamide-2-methylpropane sulfonic acid in a weight ratio of 1:1, and the rest is the same as Preparation Example 4.

[0042] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 4 is that the viscosity modifier consists of allyl glycidyl ether and 2-acrylamide-2-methylpropane sulfonic acid in a weight ratio of 1:3, and the rest is the same as Preparation Example 4.

[0043] Preparation Comparative Example 5 The difference between Preparation Comparative Example 5 and Preparation Example 7 is that an equal amount of ethylene-vinyl acetate copolymer emulsion is replaced by methylphenyl silicone resin emulsion, and the rest is the same as Preparation Example 4.

[0044] Preparation Comparative Example 6 The difference between Preparation Comparative Example 6 and Preparation Example 7 is that an equal amount of methylphenyl silicone resin emulsion is replaced by an aqueous polyurethane emulsion, and the rest is the same as Preparation Example 4.

[0045] Preparation Comparative Example 7 The difference between Preparation Comparative Example 7 and Preparation Example 7 is that an equal amount of 1,4-butylene dimethacrylate is used as methylphenyl silicone resin emulsion, and the rest is the same as Preparation Example 4. Example

[0046] Example 1 Example 1 discloses a process for preparing a non-woven polishing pad, comprising the following steps: S1, using the pretreatment agent prepared in Preparation Example 1 to treat a 1.5 mm thick, 350 g / m 2 The dry-formed polyester non-woven fabric is soaked at a temperature of 50° C. for 20 minutes, and then drained to obtain a pretreated polyester non-woven fabric; S2. Use commercially available aqueous polyurethane impregnation liquid to impregnate the pretreated polyester non-woven fabric, control the impregnation temperature to 70°C, and after impregnation for 30 minutes, use a rolling device to roll at a speed of 2m / min and a pressure of 0.2KPa to squeeze out excess aqueous polyurethane impregnation liquid, and then dry at a temperature of 70°C for 2h to obtain an impregnated polyester non-woven fabric.

[0047] S3. The prepared impregnated polyester non-woven fabric is shaped under steam conditions at a temperature of 160°C, and then sanded using a sanding device with a roughness of 400 mesh, and the impregnated polyester non-woven fabric is slotted using a slotting device, the slot width is 1mm, and the slot size is 10*10mm, and then water-based and dried at a temperature of 80°C for 60 minutes, and cut to obtain a non-woven fabric grinding pad; wherein, the commercially available water-based polyurethane dipping solution is Xinyi Synthetic PU667.

[0048] Embodiment 2-4 The difference between Example 2-4 and Example 1 is that the process parameters are different, and the sources of the pretreatment agent and the aqueous polyurethane impregnation liquid are also different, see Table 3 below for details.

[0049] Table 3 Parameters of Examples 1-4 Embodiment 5-9 The difference between Examples 5-9 and Example 2 is that the sources of the aqueous polyurethane impregnation liquid are different, see Table 4 below for details.

[0050] Table 4 Sources of aqueous polyurethane impregnation solutions of Examples 5-9 Examples 10-13 The difference between Examples 10-13 and Example 2 is that the sources of the pretreatment agents are different, see Table 5 below for details.

[0051] Table 5 Sources of pretreatment agents of Examples 1-13 Example Source of pretreatment agent Example 10 Preparation Comparative Example 1 Embodiment 11 Preparation Comparative Example 2 Example 12 Preparation Comparative Example 3 Embodiment 13 Preparation Comparative Example 4 Comparative Example Comparative Example 1 The difference between Comparative Example 1 and Example 2 is that the polyester non-woven fabric is not subjected to the immersion treatment in step S1, but is directly impregnated with the aqueous polyurethane impregnation liquid, and the rest is the same as Example 2.

[0052] Performance testing The following is a performance test of the non-woven polishing pads prepared in Examples 1-13 and Comparative Example 1: 1. Hardness test: Use a Shore A hardness tester to test the hardness of the non-woven abrasive pad, and record the test results; 2. Grinding rate test: Use grinding equipment, control grinding equipment parameters: grinding upper grinding disc speed is 40r / min, grinding lower grinding disc speed is 40r / min, grinding pressure is 0.55Mpa; grinding product silicon wafer specifications: diameter 100±0.5mm, thickness 400±1μm; use commercially available grinding fluid for rough grinding, the commercial grinding fluid comes from Jizhi Electronics semiconductor silicon wafer grinding fluid, control grinding time to 3min, and perform performance test on silicon wafer after grinding; use GB / T 6618-2009 "Silicon wafer thickness and total thickness change test method" 3.1 discrete point measurement method to measure the thickness of the same position of silicon wafer material before and after grinding, and then calculate, grinding rate (unit: nm / min) = (thickness before grinding-thickness after grinding) / grinding time, test and calculate test results; 3. Water permeability test: According to the test method in GB / T4689.22, calculate the water permeability (T, unit mL / cm) of 50mL of deionized water flowing through the sample surface. 2 h), calculate the water permeability of the sample according to T = 1800000 / (100t1-50t0), where t1 is the time for 50mL of water to pass through the sample, and t0 is the time for 50mL of water to flow without a sample, and test and calculate the test results; 4. Compression elasticity test: Use a compression tester with a load of 1kg to perform a compression test on the non-woven abrasive pad. After compressing for 2 minutes, cancel the compression and let it stand for 5 seconds to test the compression elasticity of the non-woven abrasive pad (unit: %). Compression elasticity = thickness after compression / thickness before compression * 100%. Test and record the test results. The following are the performance test data of the non-woven abrasive pads of Examples 1-13 and Comparative Example 1, see Table 6 below for details.

[0053] Table 6 Performance data of nonwoven polishing pads of Examples 1-13 and Comparative Example 1 Combining Example 1, Examples 2-4 and Comparative Example 1 and Table 6, it can be seen that in Example 1, the non-woven polishing pad is prepared using the pretreatment agent prepared in Preparation Example 1 and the commercially available aqueous polyurethane impregnation liquid. Compared with the non-woven polishing pad prepared by pretreatment without using the pretreatment agent in Comparative Example 1, the hardness is significantly improved, the elastic modulus is reduced, and the grinding efficiency and water permeability are significantly reduced. This may be because when no pretreatment is performed, the aqueous polyurethane impregnation liquid is completely filled in the gaps in the polyester non-woven fabric, so that the water permeability and grinding efficiency of the non-woven polishing pad are reduced; and compared with Example 1, Examples 2-4 are further optimized by using the aqueous polyurethane impregnation liquid prepared in the present application to impregnate the polyester non-woven fabric, and the hardness of the non-woven polishing pad obtained is improved, the compression elastic modulus is also improved, and the grinding efficiency and head water permeability are also improved, indicating that the use of the pretreatment agent and the aqueous polyurethane impregnation liquid of the present application has good synergistic synergy.

[0054] Further combined with Example 2 and Example 5-9 and Table 6, it can be concluded that further optimizing the components and ratios of the aqueous polyurethane impregnation solution applied for can improve the comprehensive performance of the non-woven polishing pad obtained; specifically, compared with Example 2, Example 5-6 further optimizes the components and ratios of the viscosity modifier, so that the hardness of the non-woven polishing pad obtained is improved, the compression elastic modulus is also improved, and the grinding efficiency and head water permeability are also improved, indicating that the preferred weight ratio of allyl glycidyl ether and 2-acrylamide-2-methylpropanesulfonic acid as viscosity modifiers has a good synergistic effect; while in Examples 7-9, the performance of the non-woven polishing pad obtained by changing the component compounding system of the aqueous polyurethane emulsion, methylphenyl silicone resin emulsion, ethylene-vinyl acetate copolymer emulsion and 1,4-butanediol dimethacrylate is reduced, which shows that optimizing the ratio of the above four can play a good synergistic role and improve the hardness, water permeability, compression elastic modulus and grinding efficiency of the non-woven polishing pad obtained.

[0055] Further combined with Example 2 and Examples 10-13 and Table 6, it can be concluded that further optimizing the components and ratios of the pretreatment agent of the present application can significantly improve the water permeability and grinding efficiency of the prepared non-woven polishing pad; in Examples 10-13, changing the ratio components of the pretreatment agent reduces the synergistic effect between the components, so that the water permeability and grinding efficiency of the non-woven polishing pad are significantly reduced, and the overall hardness is improved. This may be because the use of the pretreatment agent after changing the component ratio reduces the adsorption and coagulation properties of the aqueous polyurethane impregnation solution on the surface of the polyester non-woven fiber, thereby reducing the pore structure of the non-woven polishing pad.

[0056] In summary, as attached Figure 1 As shown, the non-woven polishing pad of the present application has a fiber pore structure, so that during the grinding process, the grinding liquid can fully penetrate into the non-woven polishing pad, and has good fluidity and permeability, thereby improving the grinding efficiency and service life of the non-woven polishing pad.

[0057] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.

Claims

1. A process for preparing a non-woven polishing pad, characterized in that: The following steps are involved: S1, soaking the dry-formed polyester non-woven fabric with a pretreatment agent to obtain a pretreated polyester non-woven fabric; S2, using an aqueous polyurethane impregnation liquid to impregnate the pretreated polyester non-woven fabric, and then rolling and drying to obtain an impregnated polyester non-woven fabric; S3, shaping, sanding, slotting, washing and drying the obtained impregnated polyester non-woven fabric to obtain a non-woven fabric abrasive pad.

2. The process for preparing a nonwoven polishing pad according to claim 1, characterized in that The pretreatment agent in step S1 is prepared from the following raw materials in weight percentage: N,N-Methylenebisacrylamide 8-10% Long chain alkyl silane coupling agent 3-5% Allyl polyethylene glycol 2-3% Chitosan quaternary ammonium salt 1-3% Sodium dioctyl sulfosuccinate 1-2% Water balance.

3. The process for preparing a nonwoven polishing pad according to claim 1, characterized in that ,The soaking temperature in step S1 is 50-60°C, and the soaking time is 20-40min.

4. The process for preparing a nonwoven polishing pad according to claim 1, characterized in that The polyester nonwoven fabric in step S1 has a thickness of 1-1.5 mm and a gram weight of 300-350 g / m 2 .

5. The process for preparing a non-woven polishing pad according to claim 1, characterized in that The aqueous polyurethane impregnation liquid in step S2 is prepared from the following raw materials in weight percentage: Water-based polyurethane emulsion 30-40% Methyl phenyl silicone resin emulsion 5-8% Ethylene-vinyl acetate copolymer emulsion 3-6% Filler 10-15% 1,4-Butanediol dimethacrylate 3-5% Viscosity modifier 2-4% Curing agent 1-3% Water balance.

6. The process for preparing a nonwoven polishing pad according to claim 1, characterized in that , the filler is white carbon black and / or zinc oxide.

7. The process for preparing a nonwoven polishing pad according to claim 1, characterized in that The viscosity modifier is composed of allyl glycidyl ether and 2-acrylamide-2-methylpropane sulfonic acid in a weight ratio of 1:(1-3).

8. The process for preparing a non-woven polishing pad according to claim 1, characterized in that , the curing agent is an isocyanate curing agent and / or an aziridine curing agent.

9. The process for preparing a nonwoven polishing pad according to claim 1, characterized in that , The immersion time in step S2 is 30-60 minutes, and the immersion temperature is 70-80°C.

10. A non-woven polishing pad, characterized in that: The invention is prepared by the preparation process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Smooth spun-bonded non-woven fabric and production process thereof

    CN114262987A

  • Non-woven fabric fiber polishing pad and preparation method thereof

    CN114395922A

  • Preparation process of felt belt for vibrating knife cutting machine and product

    CN118269383A

  • Soft water cotton fabric and preparation method thereof

    CN118704152A

  • Polishing pad and production method and polishing method of polishing pad

    JP2017185560A